Combination Foot Care and Massage Reducing Peripheral Neuropathy Symptoms in Clients With Diabetes Mellitus - Auliya, Arida; Hartinah, Dewi; Jauhar, Muhamad; Lasmini, Lasmini (Journal of Bionursing, 2025)
Diabetes Mellitus (DM) is the most challenging public health problem in the 21st century. This disease is classified as chronic, and its treatment is a challenge for the global health care system. The increasing prevalence of DM is a side effect of the transformation of life. The rise in DM complications has a serious impact on the quality of life of DM clients. Complications of this disease continue to worsen the client's condition if they do not receive appropriate intervention, leading to dysfunction in almost every organ of the body. DM complications account for the largest portion of the National Health Insurance (JKN) program's medical expenses. The aim of this study was to analyze the effect of a combination of foot care and massage on symptoms of peripheral neuropathy in DM clients. The research design used a quasi-experimental pre-posttest with a control group. The independent variable is a combination of foot care and massage, while the dependent variable is the symptoms of peripheral neuropathy. This study was conducted on diabetes mellitus in April 2025. The study sample consisted of 14 DM clients for each intervention and control group, using a purposive sampling technique based on inclusion and exclusion criteria. The research instrument used was 10 g monofilament. Combination therapy foot care and massage are given 3 times per week for 2 weeks, with a duration of 25-30 minutes per session. Data analysis used the Wilcoxon test and the Mann-Whitney test. The results of the study showed that there was a combined effect of foot care and massage on symptoms of peripheral neuropathy in DM clients with a p-value of 0.000 (p<0.05). Combination therapy/foot care and massage has a positive effect in reducing symptoms of peripheral neuropathy in DM clients. Follow-up is needed to integrate this combination therapy with community health activities, especially for DM clients.